REPEATED LIVER TRANSPLANTATION: EXPERIENCE OF RUSSIAN SCIENTIFIC CENTER OF RADIOLOGY AND SURGICAL TECHNOLOGY (RSCRST) - D. A. Granov; V. V. Borovik; F. K. Zherebtsov; V. N. Polysalov; D. N. Maistrenko; I. O. Rutkin; I. I. Tileubergenov; S. V. Shapoval (Вестник трансплантологии и искусственных органов)
The article gives the report about the experience in repeated liver transplantation (LT). Totally 99 LT including 6 repeated operation at five patients performed between june 1999 and june 2011. In 3 of 6 cases bile ducts necroses was the indication to repeated LT. Retransplantations were connected with difficulties, enlargement of duration and replacement therapy volume, also explained high number of complication after operation. It is demonstrated that chronic biliary infection and bad condition of patients are the main reasons of complication and poor prognosis after repeated liver transplantation.